Hubungan Aktivitas Fisik dengan Status Gizi Anak Sekolah Dasar pada Masa Pandemi Covid-19 di SD Negeri Maradekayya 2 Kota Makassar - Sherina Dika Aprillia; Rosdianah Rahim; Utami Murti Pratiwi; Abdul Rahman (Universitas Islam Negeri Alauddin Makassar, 2024)
Nutrition is essential to a person's growth and development, especially in elementary school children. This study aimed to determine the relationship between physical activity and the nutritional status of elementary school-age children during COVID-19 at SD Negeri Maradekayya 2 Makassar. The method was quantitative research with an observational analytic design through a cross-sectional approach. The population used was students in grades 4, 5, and 6, with a total sample of 41 students using a total sampling technique. Results of the study showed that 11 children (27%) with low physical activity, 26 children (63%) with moderate physical activity, and two children (5%) with high physical activity had good nutritional status for Elementary school-age children, with two children (5%) were excess. The results of the Chi-Square test obtained a p-value of 0.614. This study concluded that their physical activity was mainly in moderate frequency, and they were in good nutritional status. There was no significant relationship between children's physical activity and the nutritional status of elementary school-age children at SD Negeri Maradekayya 2 Makassar City during the COVID-19 pandemic.